If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2c + 9 = 19 Reorder the terms: 9 + -2c = 19 Solving 9 + -2c = 19 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2c = 19 + -9 Combine like terms: 9 + -9 = 0 0 + -2c = 19 + -9 -2c = 19 + -9 Combine like terms: 19 + -9 = 10 -2c = 10 Divide each side by '-2'. c = -5 Simplifying c = -5
| -8x+3=29+2x | | 6(2x+2)=-6 | | 2x^2-5x-20=0 | | 4+8x-3x-1-2= | | 7n-8=3n+4 | | -10y-2y=64 | | -16x^2-x+225=0 | | 8+7x-5-2x= | | 2x+6=3x+8 | | 7a+2=-26 | | 5(6x+3)=3(2x-2) | | x^4-5x^3=14x^2 | | 6b+10=-2 | | 7x-3x^2=2 | | 7x-36=6x+3 | | 6y+6=18 | | -16x^2+80x=100 | | -4x+9=-39 | | b/1+6=2 | | -x+6=-21+8x | | u=3(5-u)+1 | | 4+6x=-62 | | 3(3x-4)=2x-8 | | 4t+3(2-t)=13 | | 2+7x=-5 | | -6(3x+6)+2= | | 3x+4=-5+2x | | -7x-8=-71 | | -7-2x=-9 | | (2t^2-t-6)(2t^2+2t-1)= | | 7(2y-3)=-16 | | -5+4x=35 |